Pro2Booth: Towards an Improved Tool for Capturing Prototypes and the Prototyping Process. (May 2022) - Giunta, L.; Gopsill, J.; Kent, L.; Goudswaard, M.; Snider, C.; Hicks, B.
Abstract: The act of prototyping is a key element of the design process. However, capturing information on how prototypes evolve and influence one another is a complex problem. This paper presents an iterative evolution to a prototyping capture platform, termed Pro2Booth, designed to address the shortcomings encountered in previous systems. The Pro2Booth hardware and online software described in this paper provide a new baseline for future innovation and exploration of the prototype capture process.